Death and funeral practices in Poland - Kubiak, Anna E.; Długozima, Anna; Wedeł-Domaradzka, Agnieszka (Routledge international focus on death and funeral practices, 2024)
"This book provides a shortform definitive reference text on funerary practice in Poland. An overview of the important features of the Polish funeral law, funerals, cremations, cemeteries and funeral industry, the book also covers the demographic characteristic of mortality in Poland. Drawing on original empirical research, the book is interdisciplinary which facilitates further transnational comparative research in this important topic. It is the first book to offer a broad look at the evolution and current status of Polish funerary practices. This book provides an essential summary to researchers with an interest in funeral practices in Poland. Some of the areas which are explored are the country's historical development, the contemporary legal framework and how Poland manages its cemeteries, crematoria and other death spaces. Built on original ethnographic research conducted by the authors, this book interprets the predominance of Catholic funerals, examines the relatively recent history of cremation, and contextualizes the practices of commemoration and memoralisation. This interdisciplinary book will be of interest to academics, policy makers and practitioners interested in the historic, geographic, demographic, (multi)cultural and political context in which the funerary practices in Poland have developed, as well as the technical and professional aspects of the industry"--